Immune pathogenesis in pigeons during experimental Prohemistomum vivax infection - Abuzeid, Asmaa M. I.; Hefni, Mahmoud M.; Huang, Yue; He, Long; Zhuang, Tingting; Li, Guoqing (Frontiers in Veterinary Science, 2022)
Prohemistomum vivax is a small trematode belonging to the family Cyathocotylidae, infecting fish-eating birds and mammals, including humans. However, no data on molecular identification and immune pathogenesis are available, challenging effective diagnostic and therapeutic interventions. Here, we identified P. vivax based on combined morphological and molecular data and examined histopathological lesions and the differential cytokines expression in experimentally infected pigeons. Pigeons were orally infected with 500 prohemistomid metacercariae. Intestinal and spleen tissues were harvested 2, 4, 7, 14, 21, and 28 days post-infection (dpi). Gene expression levels of eleven cytokines (IL-1, IL-2, IL-4, IL-5, IL-6, IL-10, IL-12, IL-15, IL-18, IFN-γ, and TGF-β3) were assessed using quantitative reverse-transcription PCR (RT-qPCR). We identified the recovered flukes as Prohemistomum vivax based on morphological features and the sequence and phylogenetic analysis of the internal transcribed spacer 1 (IT1), 5.8 ribosomal RNA, and IT2 region. Histopathological lesions were induced as early as 2 dpi, with the intensity of villi atrophy and inflammatory cell infiltration increasing as the infection progressed. An early immunosuppressive state (2 and 4 dpi), with TGF-β3 overexpression, developed to allow parasite colonization. A mixed Th1/Th2 immune response (overexpressed IFN-γ, IL-12, IL-2, IL-4, and IL-5) was activated as the infection progressed from 7-28 dpi. Inflammatory cytokines (IL-1, IL-6, IL-18, and IL-15) were generally overexpressed at 7-28 dpi, peaking at 7 or 14 dpi. The upregulated Treg IL-10 expression peaking between 21-28 dpi might promote the Th1/Th2 balance and immune homeostasis to protect the host from excessive tissue pathology and inflammation. To conclude, our results presented distinct cytokine alteration throughout P. vivax infection in pigeons, which may aid in understanding the immune pathogenesis and host defense mechanism against this infection.